Formalin Inactivation of Japanese Encephalitis Virus Vaccine Alters the Antigenicity and Immunogenicity of a Neutralization Epitope in Envelope Protein Domain III - Fan, Yi-Chin; Chiu, Hsien-Chung; Chen, Li-Kuang; Chang, Gwong-Jen J.; Chiou, Shyan-Song (PLoS neglected tropical diseases, 2015)
Formalin-inactivated Japanese encephalitis virus (JEV) vaccines are widely available, but the effects of formalin inactivation on the antigenic structure of JEV and the profile of antibodies elicited after vaccination are not well understood. We used a panel of monoclonal antibodies (MAbs) to map the antigenic structure of live JEV virus, untreated control virus (UCV), formalin-inactivated commercial vaccine (FICV), and formalin-inactivated virus (FIV). The binding activity of T16 MAb against Nakayama-derived FICV and several strains of FIV was significantly lower compared to live virus and UCV. T16 MAb, a weakly neutralizing JEV serocomplex antibody, was found to inhibit JEV infection at the post-attachment step. The T16 epitope was mapped to amino acids 329, 331, and 389 within domain III (EDIII) of the envelope (E) glycoprotein. When we explored the effect of formalin inactivation on the immunogenicity of JEV, we found that Nakayama-derived FICV, FIV, and UCV all exhibited similar immunogenicity in a mouse model, inducing anti-JEV and anti-EDII 101/106/107 epitope-specific antibodies. However, the EDIII 329/331/389 epitope-specific IgG antibody and neutralizing antibody titers were significantly lower for FICV-immunized and FIV-immunized mouse serum than for UCV-immunized. Formalin inactivation seems to alter the antigenic structure of the E protein, which may reduce the potency of commercially available JEV vaccines. Virus inactivation by H2O2, but not by UV or by short-duration and higher temperature formalin treatment, is able to maintain the antigenic structure of the JEV E protein. Thus, an alternative inactivation method, such as H2O2, which is able to maintain the integrity of the E protein may be essential to improving the potency of inactivated JEV vaccines.